We argue instead as follows. Suppose $\phi$ is a ring homomorphism from $\mathbb Z$ to $\mathbb Z[i]\setminus \langle 3+i \rangle$.
Notice first that the identity $1_{R'}$ in the codomain is given by $1_{R'} =1 + \langle 3+i \rangle$, and therefore, by the properties of ring isomorphisms, $\phi(1) = 1 + \langle 3+i \rangle$.
Now, let $j \in \mathbb Z[i]\setminus \langle 3+i \rangle$. Then $j = a+bi + \langle 3+i \rangle$, with some $a,b \in \mathbb Z$. But notice that $i \equiv -3 \mod 3+i$, therefore, $a+bi + \langle 3+i \rangle = a-3b + \langle 3+i \rangle$. Let $a-3b = z$.